2018
DOI: 10.1155/2018/1709182
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Essential Oil: A Preliminary Study for the Evaluation of the Brain Effects

Abstract: We examined the effects of essential oil from legal (THC <0.2% w/v) hemp variety on the nervous system in 5 healthy volunteers. GC/EIMS and GC/FID analysis of the EO showed that the main components were myrcene and β-caryophyllene. The experiment consisted of measuring autonomic nervous system (ANS) parameters; evaluations of the mood state; and electroencephalography (EEG) recording before treatment, during treatment, and after hemp inhalation periods as compared with control conditions. The results revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…The EOs yield was 0.5 and 0.55% (vol/wt), respectively for Chinese accession and fibrante variety, well above the yield average obtained by several strains of hemp dried flowering top (0.13–0.30% vol/wt) (Gulluni et al, ; Nissen et al, ). However, the quality and quantity of EO in dried flowering tops depends on many factors, such as the accession type, its origin, genotype, soil type and climate, but also plant density and pollination (Nissen et al, ).…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…The EOs yield was 0.5 and 0.55% (vol/wt), respectively for Chinese accession and fibrante variety, well above the yield average obtained by several strains of hemp dried flowering top (0.13–0.30% vol/wt) (Gulluni et al, ; Nissen et al, ). However, the quality and quantity of EO in dried flowering tops depends on many factors, such as the accession type, its origin, genotype, soil type and climate, but also plant density and pollination (Nissen et al, ).…”
Section: Resultsmentioning
confidence: 64%
“…This data could play a key role in the neuroactive effects of these EOs because it has already been shown that the oral administration of β‐caryophyllene attenuates acute and chronic pain in mice via oppioid and endocannabinoid systems (Gulluni et al, ; Paula‐Freire, Andersen, Gama, Molska, & Carlini, ).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Henola can also be grown to obtain other substances. The analyses showed that its inflorescences contain on average 0.32% of essential oils and 0.07% of CBD, which are increasingly often used in medicine [Gulluni et al 2018, Mannucci et al 2017. Moreover, this cultivar is characterized by a very low content of THC (0.013%), one of the psychoactive substances typical in Cannabis L.…”
Section: Introductionmentioning
confidence: 99%
“…Andre et al (2016);Gulluni et al (2018) Cynodon dictylon analgescis, diuretic, anti-inflammatory, antimicrobial, hepatoprotective and anti-convulsiveAsthana et al (2012) Cyperus rotundus anti-diabetic, anti-diarrheal, anti-mutagenic, antimicrobial, anti-oxidant, anti-pyretic and…”
mentioning
confidence: 99%